Pregled vegetacijskih istraživanja u šumama hrasta crnike(Quercus ilex L.) na pokusnim plohama u Hrvatskoj : Overview of vegetation research in Holm oak forests (Quercus ilex L.) on experimental plots in Croatia - Barčić, Damir (Array, 2021)
In the vegetative sense, holm oak forests are an integral part of the Mediterranean region, with holm oak appearing as the dominant tree species in the climatogenic community of the coniferous belt. The course of vegetation development, i.e. progression and regression, is seen in the succession of holm oak forests. Succession is present on the Croatian coast of the Adriatic Sea, and throughout the whole Mediterranean area. This paper provides an overview of the vegetation analyses and dynamics of development of holm oak forests. Research was conducted only on MAB plots and plots on Rab Island (Kalifront Peninsula, belonging to the Faculty of Forestry, University of Zagreb for the research of Rauš, Španjol and Barčić). Vegetation inventory generated a list of all plant species in the tree, shrub and undergrowth layers that were observed and recorded on the selected plots, with values for abundance (number) and cover. The combustibility and flammability of holm oak were analysed, since forest fires are the most significant threat to forest vegetation and vegetation in general in the Mediterranean zone. Multifactor analysis of variance (Sokal & Rohlf, 1995) was applied to determine the flammability and combustibility for holm oak. Linear correlation analysis was applied to examine the relationship between individual variables. The course of vegetation development, i.e. progression and regression, shows the succession of holm oak forests (Figure 5). The figure indicates the long time period necessary for the succession of forest vegetation, particularly in the case of progressive succession and complete species conversion. This includes at least several rotations of pine stands, and is in direct correlation with the habitat conditions. The research of holm oak forests on the permanent experimental plots is particularly important. These plots are part of the international Man and Biosphere project (MAB). Vegetation research in holm oak forests can be compared